JOSEPH SCACHT, TEORI SKEPTISISME HADIST DAN BANTAHAN SARJANA MUSLIM TERHADAPNYA (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2022)
This paper examines Joseph Schacht's skepticism about the originality of the hadith and the objections of Muslim scholars to the theory developed by the orientalists. The writing method uses a literature review based on related references. Schacht's work,